Leadership in Action: Next Generation: What Leaders Need to Know About the Millennials - Downing, Kris (Center for Creative Leadership, 2006)
As the most recent generation enters the workforce, the challenge for leaders is not only to understand the differences between the generations but also to embrace their different perspectives and find ways to bring out the best in everyone.